Comparative Analysis of Facade Work Using Kumkang Precast, Concrete Precast, and Curtain Wall Methods in terms of Cost and Time - Maria Siwi Tiarasari; Irriene Indah Susanti (Neutron, 2022)
The development of the construction world in terms of innovation has become one of the methods of supporting success to gain advantages in terms of cost and time, one of which is the outer wall which can generally categorize into cast-in-situ and precast methods. (1) Comparison of the cost of implementing precast kumkang materials, precast concrete facades, and curtain wall facades. The precast kumkang method is 24% cheaper than the precast concrete method, the precast kumkang method is 87% cheaper than the curtain wall method, and the precast concrete method is 52% cheaper than the curtain wall method. Sorted from the cheapest to the most expensive are precast kumkang facades, precast concrete facades, and curtain wall facades. (2) Comparison of the working time of precast kumkang materials, precast concrete facades, and curtain wall facades with the results, namely curtain wall facades for 31 weeks, kumkang material precast facades for 53 weeks, and precast concrete facades for 55 weeks. Sorted from the fastest to longest, namely curtain wall facades, precast kumkang material facades, and then precast concrete facades.